THE ESSENCE OF HOMONYMS IN THE KARAKALPAK LANGUAGE - Kaljanov, Ali (Журнал иностранных языков и лингвистики, 2021)
In the scientific and linguistic literature, the essence of homonymy is understood ambiguously. Homonyms, like polysemy, is a resource for improving the expressive and visual qualities of speech. Since in the case of homonymy we are dealing with the semantic side of the word, to the extent that the expressive possibilities of homonyms relate primarily to the semantic, meaningful side of the statement, and sometimes even the whole text.